An Overview Of Temperature And Quality Of Packed Red Cell (PRC) Components Based On Distance And Delivery Time - Panggayuh, Ardi; Sudiwati, Ni Luh Putu Eka; Ariani, Nia Lukita; Nadhifah, Azizatun; Rif'ati, Septi Laily (Universitas Tribhuwana Tunggadewi, 2024)
The Indonesian Red Cross is responsible for the distribution of blood products to hospital blood banks. The daily blood distribution route will vary due to the fact that the number of blood requests and the number of hospital blood banks vary on a daily basis. The implementation of a cold chain system is one method of optimizing blood distribution and transportation activities. The objective of this investigation is to evaluate the temperature and quality of PRC components in relation to their delivery time and distance. This research method is quantitative-descriptive. The population of this study consisted of all blood that was donated to the hospital blood bank in Sidoarjo Regency between October and November 2022. The blood sample used in this study was collected from the UDD PMI Sidoarjo Regency. The sampling technique of accidental sampling would be employed to visually identify the quality of PRC and temperature. The results of this study indicated that 460 PRC bags were delivered to three hospital blood banks in the UDD PMI Sidoarjo Regency. The PRC did not experience lysis, and 50 bags (10.86%) of the 460 PRC bags experienced a temperature change of over 10 °C. Conclusion: The temperature of the dropped PRC components is influenced by the delivery time and distance. The SOP must be strictly adhered to by all officers who distribute and transport blood to guarantee that the quality of the blood remains in good condition.